IMPLEMENTASI KEBIJAKAN SISTEM PELAYANAN INFORMASI DAN PERIZINAN INVESTASI DI BADAN KOORDINASI PENANAMAN MODAL PROVINSI SULAWESI UTARA - Saragih, Eli Kristian; Rares, Joyce Jacinta; Ruru, Joorie Marhaen (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstrak: The system of Licensing and Investment information services Electronically (SPIPISE) is theinnovation of public service that aims to bring about the licensing service and non-licensing better. Thesystem of Licensing and Investment information services electronically allows investors to do simplylicensing arrangements, cheap, efficient, and predictable. The system of Licensing And Investmentinformation services Electronically also provides convenience for officers of the capital investmentCoordination Agency (BKPM) and Integrated Service of one door (PTSP) to do the validation and get datain processing the application for the investment into capital investment coordination board authority norone door Integrated Services. The system of Licensing and Investment information services electronicallyhas three (3) main menu; information capital investment, capital investment and Supporting Services.Implementation of the system of Licensing and Investment information services electronically viewed from4 implementation theory according to Edward III, namely: communication, resources, attitudes andbureaucratic structure. This research uses descriptive method of kualitatif approach through an in-depthinterview to 10 (ten) informants, observation and search additional documents in the form of a list ofguidelines for interviewing, recording device and stationery to write. The results showed that in general thesystem of Licensing and Investment information services electronically has not gone well.Key words: Implementation of Licensing and Investment Information ServicePENDAHULUANMenghadapi Era Globalisasi yangpenuh dengan